Retrospective analysis of immediate and long-term results of NOSES technique and conventional laparoscopic-assisted resection in patients with colorectal cancer - Malev, Sergei; Zhang, Hao; Yuan, Ziming; Tang, Qingchao; Wang, Guiyu; Oganezov, Giorgi; Huang, Rui; Wang, Xishan (Frontiers in Surgery, 2024)
IntroductionThe aim of research was to study the feasibility and safety of surgery providing specimen extraction through natural orifices in patients with colorectal cancer.Materials and methodsThis study is a comparative retrospective analysis of findings obtained from 265 patients who underwent surgical treatment using NOSES technique and 275 patients who underwent laparoscopic-assisted (LA) resection. Data included preoperative patients’ information, intraoperative findings, results of postoperative pathological examination of surgical specimens, early postoperative period analysis, and follow-up.ResultsBoth groups were comparable in terms of gender, age and BMI. The duration of surgery was similar in both groups (p = 0.94). Intraoperative blood loss under NOSES interventions was slightly lower than in laparoscopic-assisted surgeries (p < 0.001). There was no significant difference in the number of lymph nodes removed and anal function scores between the two groups (p > 0.05). It was revealed that in the NOSES group, the function of the gastrointestinal tract normalized at an earlier time, slightly the time to start liquid food intake and the duration of postoperative hospital stay were reduced (p < 0.001). A statistically significant difference between groups was found in complications, such as pneumonia (p = 0.03). The absolute number of complications was observed more often in the LA surgery group (10.4%) than in the NOSES group (5.8%). Local recurrence was less common in the NOSES group (p = 0.01). There were no statistically significant differences in disease progression (p = 0.16). When analyzing disease-free and overall survival rate in this study, there was no statistically significant difference between the two surgical techniques in terms of their effect on postoperative survival (p > 0.05).ConclusionThe results of this study demonstrate that NOSES technique is a relatively safe and effective surgical option in patients with colorectal cancer. It has high surgical efficiency providing no increased risk of surgical intervention, reducing total number of postoperative complications, reducing duration of postoperative hospital stay, reducing the time for gastrointestinal function recovery and the start of food intake. This study supports that NOSES has clear advantages over conventional laparoscopic-assisted surgery.